Archaeological elite indicators from 1st Millennium AD Östergötland - Rundkvist, Martin (Information not available, contact SND for more information, 2014)
The Swedish province of Östergötland has long been recognised as one of the 1st millennium's political hot spots. Splendid single finds, though never before surveyed comprehensively, offer a rough idea of where elite settlements might be sought. Not one of the ostentatious manorial buildings where the era's elite lived has, however, been identified in the field. This study aims at beginning to remedy the regional absence of mead-halls, being an investigation of the internal political geography of Östergötland during the period AD 375-1000. The data of this study present a compilation of geographical, temporal, contextual and other information on artefacts and ancient monuments, which have been interpreted as indicators of elite settlements, spanning from the Late Roman Period to the Viking Age. The dataset includes data from previous excavations and surveys, as well as new data collected through excavation and metal detecting during 2003-2008.

Purpose:

These archaeological data were collected in 2003-2009 for the purpose of identifying elite settlements in the Swedish province of Östergötland during the 1st Millennium AD.

The dataset is comprised of a spreadsheet with information on ancient monuments, stray finds, hoards and contextual finds, which indicate the presence of an elite settlement. Data was collected from literature and museums collections, as well as from archaeological field work such as excavation and field surveying. Seventeen sites were surveyed with metal detectors, discriminating against iron. At three of the sites excavation trenches were opened. Features and finds were given coordinates with a hand-held GPS or a total-station. When no more precise information on location has been available, than on which hamlet's land a find has been made, the coordinates of each hamlet's current main house have been used.Uppgifterna innefattar bland annat inventarienummer, geografiskt läge, datering, typ och kontext. The information includes inventory number, geographical position, dating, type, amount and context. The data can be downloaded in XLSX or CSV format.

Östergötland har länge uppfattats som ett av den yngre järnålderns politiska centralområden. Enskilda praktfynd ger en ungefärlig indikation på var elitens bosättningar kan ha legat, men ingen samlad och ingående översikt av dessa fynd har tidigare gjorts. Inte en enda hallbyggnad tillhörande en sådan elitbosättning har heller identifierats i fält inom landskapet. Denna studie syftar till att att börja åtgärda den regionala frånvaron av hallbyggnader i det arkeologiska materialet genom att undersöka Östergötlands politiska geografi under perioden 375-1000 e. Kr. Datamaterialet är en sammanställning av geografisk, tidsmässig, kontextuell och annan information om fynd och fornlämningar från yngre romersk järnålder till vikingatid, vilka tolkats som indikatorer på elitbosättningar i den undersökta regionen. I detta ingår såväl äldre uppgifter från tidigare undersökningar som nya data från arkeologiska undersökningar och metalldetekteringar som genomförts under åren 2003-2008.

Syfte:

Dessa arkeologiska data samlades in under åren 2003-2009 för att spåra var den politiska eliten höll till i Östergötland under den yngre järnåldern.

Datasetet består av en tabell med information om fornlämningar, lösfynd, depåfynd samt kontextanknutna fynd, vilka indikerar förekomsten av en elitbosättning i det undersökta området. Sammanställning av äldre uppgifter från litteratur och museer samt datainsamling genom arkeologisk undersökning och fältinventering. Metalldetektering genomfördes på sjutton arkeologiska lokaler, där järnindikationer särskildes från andra metaller. Vid tre lokaler drogs också undersökningsschakt. Inmätning av anläggningar och fynd gjordes med GPS eller totalstation. Om ingen mer noggrann lägesinformation har funnits tillgänglig än på vilken bys mark ett fynd har påträffats, har koordinaterna för byns aktuella huvudbebyggelse använts. Data går att ladda ned antingen i XLSX- eller CSV-format.
Arkeologiska elitindikatorer från Östergötlands yngre järnålder
Keywords: archaeology; arkeologi; Iron Age; järnålder; Roman Iron Age; romersk järnålder; Late Iron Age; yngre järnålder; Migration Period; folkvandringstid; Vendel Era; vendeltid; Viking Age; vikingatid; political geography; politisk geografi; HISTORY; HISTORIA; Archaeology; Arkeologi